Effect of accumulated dust on the performance of solar PV module - Nipu, Naznin Nahar; Saha, Avijit; Khan, Md. Fayyaz (International Journal of Engineering and Technology, 2016)
A Solar panel is rated such that it can yield optimum output under Standard Testing Conditions (STC). But due to different environmental factors the efficiency of the panel is reduced gradually after installation. Accumulation of dust on solar PV panel is one such natural phenomenon. When dust accumulates on the PV panel, the temperature of the cells increases which subsequently decreases the open circuit voltage. The short circuit current is also reduced as deposition of dust causes shading on the panel surface. As a result, the output power of the module decreases. In this paper, the effect of dust on the performance of the photovoltaic module has been studied. The increase in temperature due to dust accumulation has been visualized through the thermal camera and the reduction in power has been analyzed through PSpice simulation and experimental data for the different amount of dust accumulated.